The role of the communicative approach in the modern methodology of teaching foreign languages. - Hladkoskok, Lesia; Sobkov, Yuriy; Cherska, Zhanna; Bukhinska, Tetiana (AD ALTA: Journal of Interdisciplinary Research (14/01-XLII.). Social Sciences., 2024)
In today's multilingual world, understanding the role of the communicative approach in the methodology of teaching foreign languages is key to ensuring the effectiveness of educational processes. The purpose of the article is an in-depth analysis of the influence of the communicative approach on the process of teaching foreign languages, the identification of the main advantages of this method and the development of recommendations for its optimization. The methodology involves a comprehensive approach, which includes the analysis of the experience of international educational programs, market assessment and the practice of applying the communicative approach. The results revealed that the communicative approach significantly increases student motivation and the level of involvement in the educational process. The study indicates the need to adapt the communicative approach to the specifics of the cultural and linguistic environment of students, which turned out to be a significant challenge in multinational classes. The practical significance lies in the integration of modern technologies into the communicative process, as it requires a high level of technological training from teachers. The article outlines the role of intercultural aspects and the development of inclusive educational practices, which require a flexible approach and openness to continuous professional development from educational institutions. A number of recommended measures to improve the teaching of foreign languages using a communicative approach are provided. Prospects for further research are the development of modular educational programs that would enable individualization of the educational process and consideration of cultural characteristics of students
Keywords: communicative approach,; teaching foreign languages,; interactive methods; speech competence,; group interaction,; authentic materials,; educational technologies.